2016
DOI: 10.1002/j.2334-5837.2016.00187.x
|View full text |Cite
|
Sign up to set email alerts
|

“Fifty Shades of Agile”: AN ANALYSIS OF DIFFERENT PERSPECTIVES OF AGILE SYSTEMS ENGINEERING

Abstract: Although Agile is well‐defined, and relatively widely‐used within the software engineering field, applying Agile to Systems Engineering (SE) is still under debate. While some feel that Agile SE offers potential to improve customer satisfaction and reduce cost, risk and time to market, it is unclear how well Agile approaches apply to SE. This paper explores diverse rationales for applying Agile SE, various types of systems it can be applied to, and different Agile SE approaches, showing that there is no single … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…ASE does not refer to a specific approach as there is no single, commonly accepted definition of or process that can be authoritatively referred to as agile systems engineering. In fact, Kemp et al have identified four distinct ways that the term agile SE is used (Kemp, Akroyd-Wallis, et al 2016):…”
Section: Agile Systems Engineeringmentioning
confidence: 99%
“…ASE does not refer to a specific approach as there is no single, commonly accepted definition of or process that can be authoritatively referred to as agile systems engineering. In fact, Kemp et al have identified four distinct ways that the term agile SE is used (Kemp, Akroyd-Wallis, et al 2016):…”
Section: Agile Systems Engineeringmentioning
confidence: 99%
“…Many authors remark that creative Systems Engineering is both an art and a science (Ryschkewitsch et al, 2009): whilst systems architecting (Maier and Rechtin, 2009) and Systems Engineering (Haskins, 2010) contribute to the understanding of complex situations through their ability to reduce complexity. Kemp et al (2016) meanwhile observe that the movement from Computer Aided Software Engineering (CASE) to applying agile techniques to Systems Engineering (Agile Systems Engineering) has demonstrated its potential to deliver value from ideas in an agile manner, particularly in complex, adaptive situations.…”
Section: Innovation and Systems Engineeringmentioning
confidence: 99%